Age Distribution of Patients Presenting With Typhoid and Paratyphoid Fever in Kathmandu, Nepal - Gajurel, Damodar; Sharma, Rabi Prakash; Dhungana, Krishna; Acharya, Niranjan; Karki, Prasant; Acharya, Sudikshya (Journal of Nobel Medical College, 2018)
Background: Enteric fever is a significant cause of morbidity in Nepal. In the past, Salmonella entericaserovar Typhi (S. Typhi) was the major causative organism of enteric fever. However, more recently, Salmonella entericaserovar Paratyphi (S.Paratyphi) A has been isolated from most patients presenting with enteric fever in various regions of Nepal. This study aimed to evaluate age differences in patients presenting with typhoid and paratyphoid fever. Materials & Methods: Between December 2014 and October 2015, 186 patients presented with enteric fever to the Civil Service Hospital in Kathmandu. S. Typhi and S.Paratyphi A were isolated from blood cultures in 48.4% and 51.6% of the cases, respectively. Age groups of the patients infected with either serovar were compared. Results: The mean age of patients from whom S. Typhi was isolated was 19.3 years, while the mean age of patients from whom S. Paratyphi A was isolated was 25.2 years; p=0.025. Conclusion: Our study shows that age is an important factor in having either typhoid or paratyphoid fever. This will help in the prevention of typhoid and paratyphoid fever in various age groups. Journal of Nobel Medical College Volume 6, Number 2, Issue 11 (July-December, 2017) Page:25-28